Evaluation of role of fixed orthodontics in changing oral ecological flora of opportunistic microbes in children and adolescent - Chandresh Shukla; Rajkumar Maurya; Vinod Singh; Manisha Tijare (Wolters Kluwer Medknow Publications, 2017)
Objective: To determine the prevalence and counts of Streptococcus mutans and Candida species in orthodontic fixed appliance therapy patients and comparison of the efficiency of manual and electronic toothbrushes on minimizing plaque by reducing S. mutans and Candida species in above-mentioned patients. Materials and Methods: The study was carried out on total number of sixty patients scheduled for orthodontic treatment (age group: 13-18). Plaque samples were collected to determine oral carriage of S. mutans and Candida of these patients, and readings were noted at T0 (before appliance placement), 2nd and 3rd month after the placement of appliances (T1 and T2). Counts of S. mutans were determined using Dentocult SM kit. Candida was cultured on Sabouraud's dextrose agar. The participants in the study group (orthodontic patients) were then divided into two groups each of 30: Group 1 (manual toothbrush), Group 2 (electronic toothbrush), and plaque samples were taken at the end of 1st, 2nd, and 3rd month to determine the efficacy of manual versus electronic toothbrushes. Results: After orthodontic treatment, colonization of S. mutans and Candida increased dramatically. Results for S. mutans counts and Candida clearly showed superiority of electronic tooth brushing over manual tooth brushing during orthodontic treatment. Conclusion: Results clearly showed that orthodontic appliances increase colonization of S. mutans and Candida albicans in oral cavity over the period of treatment time which can be controlled with proper timely brushing. The study also concludes superiority of electronic tooth brushing over manual tooth brushing.